Konsep Pendidikan Dalam Kisah Nabi Musa as. Dan Nabi Khidir as. (Telaah QS. al-Kahfi ayat 65-82 Dalam Tafsir Al-Mishbah) - Fauzi, Nasrul; Chudzaifah, Ibnu (Tarbiyah STAIN Sorong, 2017)
This research is based on phenomena that exist today that are still incompatible with IslamicEducation expectations. According to the purpose of this study is to study the explanation of theconcept of special educators based on the story of the Prophet Musa as. and the prophet Khidr as.which is in the QS. al-Kahfi verses 65-82. This research is a literature study or literature study thatis usually done. The method used is the interpretation of tahlili results of research on interpretationand books on the story of the Prophet Musa as. and the prophet Khidr as. which is in the QS. al-Kahfi verses 65 to verse 82. In the process of analyzing and discussing this research by gatheringreference material that is questioned by the title of the study. Prophet Musa as. and the prophetKhidr as. namely in QS. al-Kahfi verses 65-82. As the concept of educators in the story of theprophet Musa as. and the prophet Khidr as. are 1) an educator must have knowledge before givinglearning to students; 2) an educator gives students requirements or regulations before conductingthe learning process; 3) an educator uses methods to deliver lessons; 4) an educator must haveethics.